Unpacking the Digital Advantage: Exploring the Impact of ICT Use and Academic Performance on EFL Students’ Reading Proficiency - Fathia Khairunnisa Khairunnisa; Weni Pratiwi; Dewi Nurholis; Chuzaimah Dahlan Diem; Machdalena Vianty (AL-ISHLAH: Jurnal Pendidikan, 2025)
Reading proficiency is essential for academic success, particularly among English as a Foreign Language (EFL) learners in higher education. As Information and Communication Technology (ICT) becomes increasingly integrated into educational practices, its potential impact on students’ reading skills warrants closer investigation. This study examines the relationship between ICT utilization, academic performance, and reading proficiency among EFL students. A correlational design was employed to analyze the association among ICT usage, Grade Point Average (GPA), and reading proficiency. Seventy-one students from an English Education postgraduate program at a state university in Palembang participated in the study. Data were collected through an ICT utilization questionnaire, official GPA records, and a standardized TOEFL reading test. Pearson Product Moment correlation and regression analyses were used to interpret the data. Findings revealed a significant positive correlation between ICT utilization and reading proficiency (r = 0.237, p = 0.046), with ICT contributing 5.6% to reading proficiency. In contrast, GPA showed no significant correlation (r = -0.039, p = 0.748) or predictive value for reading outcomes. The overall regression model was not statistically significant (p = 0.075). While ICT use demonstrates a modest but significant influence on students' reading skills, academic performance, as measured by GPA, does not. These findings underscore the importance of incorporating ICT tools into reading instruction and call for enhanced digital literacy initiatives to support reading development in EFL contexts.